In Vitro antioxidant activity of Polygonum Glabrum - Raja sundara rajan,; Ramya I, (International Journal of Phytomedicine, 2017)
Assessment of antioxidant activity was imperative in the screening of medicinal plants for potential health benefits. In present study methanol extract of Polygonum glabrum (polygonaceae) was screened for its in vitro antioxidant activity using biologically relevant methodologies which scavenge radicals such as 1,1 diphenyl 2 picryl hydrazyl (DPPH), nitric oxide, hydrogen peroxide, hydroxyl, superoxide anion and 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS). Total reducing ability by conversion of ferric (III) to ferrous (II) and molybdenum (VI) to molybdenum (V), metal ion chelating capacity and anti lipid peroxidation activities were also examined. The antioxidant ability of Polygonum glabrum whole plant extract was found to be in a dose dependent manner. The IC50 values for scavenging of DPPH● and ABTS●+ free radicals were 13.18 μg/ml and 20.46 μg/ml. For scavenging of nitric oxide, hydrogen peroxide, hydroxyl and superoxide anion radicals, the IC50 values were found to be 80.22 μg/ml, 33.06 μg/ml, 52.26μg/ml and 36.98 μg/ml respectively. Further, addition of 120μg/ml of plant extract to the reaction mixture produced 50% lipid peroxidation inhibition activity. Commercial antioxidants such as vitamin E, quercetin, butylated hydroxytoluene and ascorbic acid were used as reference compounds. The strong antioxidant activity of Polygonum glabrum may be credited to the presence of triterpenes [beta-hydroxyfriedalanol], phenols [3-hydroxy-5-methoxystilbene], flavonoids [pinocembrin and pinocembrin-5-methylether], steroids [sitosterol - (6-O-palmitoyl)- 3-O-β-D glucopyranoside and sitosterol-3-O-β-D glucopyranoside], sesqueterpenes [2,3-dihydroxy isodrimeninol] and pigments etc in methanol extract.